THE RELATIONSHIP BETWEEN PREDISPOSING FACTORS AND ANTENATAL CARE (ANC) COMPLIANCE IN PREGNANT WOMEN - Tafarel, Alifiya Fajrin; Mamuroh, Lilis; Sukmawati, Sukmawati (Journal of Maternity Care and Reproductive Health, 2025)
Maternal and infant mortality rates in Indonesia are still high. One of the factors affecting MMR and IMR is the lack of compliance of pregnant women in conducting Antenatal Care (ANC). ANC can prevent and detect early complications in pregnancy. ANC is an effort to reduce MMR and IMR which is carried out at least 6x. The objectives to determine the relationship between predisposing factors (age, education, occupation, parity, attitude, and knowledge) with ANC compliance. The study used a quantitative correlational approach with a cross sectional approach. The sample was 60 third trimester pregnant women who were taken by total sampling. The instrument was a questionnaire, which had been tested for validity and reliability by researchers Zjubaidi & Chairiyah. Bivariate analysis using Chi-square test. The results are age, parity, and attitude had a significant relationship with ANC adherence (p<0.05), while education, occupation, and knowledge did not have a significant relationship (p>0.05). Continuous public health education focusing on optimal utilization of ANC services is needed. Keywords: Pregnant woment, Antenatal Care (ANC) Compliance, Trimester III.